Effect on implementation of open and distance learning (ODL) during Covid-19 for basic structural analysis course / W.S. Wan Chik ... [et al.] - Wan Chik, Wan Syarizawani; Khalid, Noorashiekin; Mohd Zahid, Azyan Zafyrah; Saifullizam, Nadia Zalikha; Kamaruddin, Siti Farahin; Mat Zin, Mazni (2021)
COVID-19 pandemic dominates the world. It affects all sectors and the global educational systems are no exception. Based on this scenario, the Open and Distance Learning (ODL) program for the Basic Structural Analysis Course of the Civil Engineering Diploma (EC110) program analysed the data on the effect of the Movement Control Orders (MCO) on students' performance. This analysis therefore aims to assess the achievement of Program Outcomes (PO) and Course Outcomes (CO) for the semesters of September to January 2020 (face-to-face) and March to July 2020 (ODL). The findings showed the PO1 and PO2 increased by 22% for semester ODL and 1% for semester face-to-face respectively. However, CO1 and CO2 increased by 20% and 10% for semester ODL and semester face-to-face respectively. This research indicated ODL has not greatly affected the results and performance of the students during MCO. The finding demonstrated that it is possible to achieve the Course Learning Outcomes (CLO)